Shakespeare and the Jews - Shapiro, James (Columbia University Press, 2016)
First published in 1996, James Shapiro's pathbreaking analysis of the portrayal of Jews in Elizabethan England challenged readers to recognize the significance of Jewish questions in Shakespeare's day. From accounts of Christians masquerading as Jews to fantasies of settling foreign Jews in Ireland, Shapiro's work delves deeply into the cultural insecurities of Elizabethans while illuminating Shakespeare's portrayal of Shylock in The Merchant of Venice. In a new preface, Shapiro reflects upon what he has learned about intolerance since the first publication of Shakespeare and the Jews
10.7312/shap17866
Keywords: Jews / History / 16th century; Jews / History / 17th century; Jews / History / 18th century; Judaism in literature; Juden / Motiv; LITERARY CRITICISM / European / English; Irish; Scottish; Welsh